3(x/4)=7x/6

Simple and best practice solution for 3(x/4)=7x/6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(x/4)=7x/6 equation:



3(x/4)=7x/6
We move all terms to the left:
3(x/4)-(7x/6)=0
We add all the numbers together, and all the variables
3(+x/4)-(+7x/6)=0
We multiply parentheses
3x-(+7x/6)=0
We get rid of parentheses
3x-7x/6=0
We multiply all the terms by the denominator
3x*6-7x=0
We add all the numbers together, and all the variables
-7x+3x*6=0
Wy multiply elements
-7x+18x=0
We add all the numbers together, and all the variables
11x=0
x=0/11
x=0

See similar equations:

| 5k^2-10=23k | | x+33=57 | | 2u-45+2u+u+5=180 | | (x-3)^2+(+5x)^2=9 | | 3/8y=15/16 | | 75x=3.7=1.7+1.75x | | 5x^2-16=10 | | -9.5x+0.79=-6.81 | | 40+2t-48+2t-12=180 | | 12u-4u-5u=18 | | 2a+10=7-9 | | (-1/3)x+7=4 | | 2x+1/7-3x-2/4=10 | | 499-1/3=x | | 2a-9=-13 | | -y+45=29 | | (x-9)(x)=2x-5x-8 | | 2v-14+2v-20+2v-20=180 | | x-(-15.5)=19.6 | | (x-3)^2+(5x+4-4)^2=9 | | 15=-1+4f | | 37=-8t-3 | | -21x^2+77x+28=0 | | (x-3)^2+(-4)^2=9 | | x-(15.5)=19.6 | | 5=-2g+3g | | (12x+30)+(6-9x)=x | | 5(x-8)+10=25 | | 5p^2-21-20=0 | | z/7+2=-83 | | 0=3w+3w | | k/6+2=15 |

Equations solver categories